THE RELATIONSHIP BETWEEN CONDITION FACTOR AND MEAT YIELD OF WILD OYSTER CRASSOSTREA CUCULLATA BORN - Wouthuyzen, Sam; Suwartana, Atjep (Research Center for Oceanography - Indonesian Institute of Sciences (LIPI), 1984)
From April 1982 to October 1982, 393 specimens of oyster were collected near mangrove roots from Piru, Waisala, Wailale, Pelita Jaya (Seram Island) Ihamahu (Saparua Island), and Manipa Island for sondition factor analysis. The regression of meat yield (Y) on whole meat weight (X1) and condition factor (X2) could be expressed by the following equation: Y = 0.062 X1 + 0.127 X2 ? 10.975. The analysis of correlation indicated that the meat yield of oyster depends on the condition factor. Hydrologieal parameters which affected the condition factor are described.